Եզնիկ Կողբացու «Եղծ աղանդոց»-ի լեզվի մի քանի առանձնահատկությունների շուրջ - Լ. Շ. Հովհաննիսյան (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
В статье исследуются некоторые философские понятия, а также слова диалектно-разговорного слоя. В древнеармянском языке первой половины 5-го века еще не было стабильной системы философских терминов.As in the first half of the 5th century the Armenian language did not have a system of philosophical terms, Yeznik has managed to convey scientific notions with ordinary words: thus, new meanings acquired terminological value.
Keywords: Բառարանագրություն; Գրաբար